THE ROLE OF STEP-NC IN IMPROVING THE PERFORMANCE OF SUPPLY CHAIN - The Jaya Suteja (Institute of Research and Community Outreach - Petra Christian University, 2005)
The success of supply chain implementation in producing manufactured product heavily relies on the development of CAD system, CAM system, and CNC machine tool. However, current CAD system, CAM system, and CNC machine tool have some weaknesses in supporting supply chain implementation. This paper presents an overview of STEP-NC and its role in supply chain of manufactured product. STEP-NC is a new interface standard for CAD-CAM-CNC chain, which is developed by International Standards Organization (ISO) to extend STEP model data to define data for NC machine tools. By using STEP-NC, the link of all information in supply chain of manufactured product will be more flexible, faster, easier, safer, and more reliable.